Analisis Perumusan Kebijakan Peningkatan Literasi Disekolah SMPN 1 PERCUT SEI TUAN - Ahmadi Hamsa Ramadhan; Laudy Livianti; Tamimi Mujahid; Maya Masita (Politeknik Kampar, 2024)
The school literacy movement (GLS) is the result of one of the educational innovations in the field of strategy. The school literacy movement emphasizes literacy activities which include thinking skills using knowledge sources in print, visual, digital and auditorium forms. The implementation of GLS at the MI/SD level is carried out in line with strengthening the Ministry of Education and Culture Regulation (Permendikbud) Number 23 of 2015 concerning Employment Growth in an effort to create a literacy culture. There are several concepts of technical literacy in schools, including: daily, weekly, monthly and per semester.